Treatment Strategies for Chronic Cases - Susan M Lord (Pain Research and Management)
The treatment of chronic somatic pain, including pain referred to the head, neck, shoulder girdle and upper limb from somatic structures, is addressed. Levels of evidence for the various treatments that have been prescribed for chronic whiplash associated disorders are considered. The challenge to find a treatment strategy for chronic pain after whiplash that completely relieves the condition and prevents its sequelae is reviewed.